Clinical evaluation of the function of hypothalamo-pituitary-thyroid axis in children with central nervous system infections - Cui Wei; Lin Jing; Bai Taomin; Zhang Xiaoyan; Jiao Fuyong; Liu Bingweng (BMC, 2011)
Abstract Background It is well known that certain non-thyroidal critical illness may lead to euthyroid sick syndrome(ESS). There are little reports about the change of thyroid hormone in the children's central nervous system (CNS) infections. Results The results of serum TT3, TT4 and TSH in these children were compared with those in 20 cases of healthy adults and 20 cases of adults with primary hypothyroidism. Serum T3 and T4 were decreased in 34/78 children with CNS infections, T3 and T4 were much lower than those of healthy adult (p < 0.05), but still higher than that of the primary hypothyroidism (p < 0.05), and TSH levels were not significant differences among children with CNS infections and children with non-CNS infections (p > 0.05). Low T3 and T4 levels in serum and cerebrospinal fluid(CSF)were predominant in children with serious infections of CNS, 31/34 (percent 91.17) cases of serious CNS infection had low serum TT3 and/or TT4. The low T3 with low T4 was seen in 14/34 children of severe CNS infections, 3 of them died. The levels of CSF T3 (X ± SD = 0.39 ± 0.47 ng/ml) and T4 (x ± SD = 1.02 ± 1.27 ug/dl) in the serious CNS infections were lower than that of non-CNS infections T3 (x ± SD = 0.93 ± 1.23 ng/ml), and T4 (x ± SD = 2.42 ± 1.70 ug/dl), 7 died children were all in the subjects of low T3 and/or low T4. In 22 children with non-CNS infections, serum T3 and T4 levels were lower than that of healthy adult, but have not significant difference(p > 0.05). Conclusions These results suggest that detection of TT3, TT4 and TSH in serum and/or CSF simultaneous or alone in analyses would be valuable in correctly judging thyroid function and evaluating the prognosis of the children with infections of CNS. Measuring a little amount of blood (1 ml)or CSF required for this method is a simple, convenient and accurate method.